Printing poly(p-phenyleneethynylene) PLEDs - Smarsly, Emanuel; Veith, Lisa; Curticean, Ernest Ronald; Wacker, Irene; Schröder, Rasmus R.; Bunz, Uwe H. F. (ACS applied materials & interfaces, 2019)
Gravure printing of functional thin-film layers of side-chain-substituted poly(para-phenyleneethynylene)s (PPEs) is reported. Rheological properties of PPEs in combination with the Hansen solubility model allowed the formulation of enhanced single-component inks. Layer evaluation is performed with reflectometric thin-film recordings in an optical setup for laterally resolved large-area investigation using imaging color reflectometry. An organic light-emitting diode in a simple glass/indium tin oxide/poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)/PPE/LiF-Al stack was gravure-printed from the improved ink showing excellent luminance (542 cd m-2, U = 11.5 V) for this polymer class.